(untitled) (Communication & Society, 2023)
This article studies how Argentine national media outlets reported on China’s Belt and Road Initiative (BRI) between 2013 and February 2022 (this covers the period from the launch of the BRI to Argentina’s official accession to the initiative). Based on a framing analysis of 272 articles, this study argues that national media outlets tend to reproduce two frames about the BRI: they either present it as an opportunity or as a threat. The balance between them matters when attempting to understand how media organisations shape citizens’ perceptions of China and the BRI. In the case of Argentina, even though its political and economic relations with China have become closer, reports on the BRI were quite polarised. Indeed, national media outlets’ portrayal of the BRI as an opportunity has been slightly more prevalent than negative portrayal (41% vs. 35%). However, national media firms covered the BRI in different ways. Some organisations conveyed largely positive frames, some chiefly presented negative ones, and others were more balanced. The specific editorial lines of the newspapers and their affinities to national political alliances explain these different patterns. Furthermore, although articles citing Western sources were indeed more negative about the BRI, many of the op-eds and reports criticising the BRI were produced by Argentine journalists and other local actors. Thus, Chinese academics exaggerate Western media sources’ influence on Argentina’s national media critical coverage of China while overlooking reasonable concerns about the impacts of Chinese projects.